Sensorless Nonsmooth H∞-Tracking Synthesis of Servosystems with Backlash and Coulomb Friction∗. Issue 11 (2015) - Ponce, Israel U.; Orlov, Yury; Aguilar, Luis T.; Alvarez, Joaquin
Abstract: The nonsmooth phenomena such as backlash and Coulomb friction, often occurring in mechanical systems, typically produce undesired inaccuracies, oscillations and instability thereby degrading the system performance. In this paper, the H∞ synthesis is developed for a class of nonsmooth systems and it is then applied to an industrial emulator where the described phenomena are present, and an elastic band is included in the transmission motor-load, and only motor position measurements are feasible. The effectiveness of the proposed method is supported by experimental results.